Comparison of short-term outcomes between SuperPATH approach and conventional approaches in hip replacement: a systematic review and meta-analysis of randomized controlled trials - Nikolai Ramadanov; Simon Bueschges; Kuiliang Liu; Roman Klein; Ruediger Schultka (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background It remains uncertain if the new SuperPATH approach benefits patients in artificial hip joint replacement. We conducted a systematic review and meta-analysis of randomized controlled trials to compare the short-term outcome of SuperPATH approach and conventional approaches in hip joint replacement. Methods A systematic literature search up to April 2020 was performed to identify randomized controlled trials comparing SuperPATH with conventional approaches in hip joint replacement. We measured surgical, functional, and radiological outcomes. Mean differences or odds ratios with 95% confidence intervals were calculated and pooled using random effects models and the Hartung-Knapp-Sidik-Jonkman method. Results A total of 12 RCTs involving 726 patients met the inclusion criteria, one trial with a level I evidence, 11 trials with level II evidence. The overall meta-analysis showed that SuperPATH approach reduced incision length (MD = − 4.84, 95% CI − 7.04 to − 2.64, p < 0.01), pain VAS 7 day postoperatively (MD = − 1.39, 95% CI − 2.57 to − 0.21, p = 0.03), and HHS 7 day postoperatively (MD = 10.24, 95% CI 0.27 to 20.21, p = 0.05). The two approaches did not differ in acetabular cup positioning angles, intra- and postoperative blood loss, hospitalization period, and postoperative complications. Hip replacement via SuperPATH approach had a longer operation time than hip replacement via conventional approaches. Conclusions SuperPATH approach showed better results in decreasing incision length and early pain intensity as well as improvement of short-term functional outcome. Long-term outcomes of SuperPATH approach need to be investigated.